PHYSICAL ACTIVITIES LEVELS OF HIGH SCHOOL STUDENTS AT SESI BARRA FORTALEZA (Fiep Bulletin - online, 2015)
Young scholars hardly show cronic-degenative dysfunctions. That's why we must do efforts to prevent bad habits in this age this period do not appear the syntoms from these pathologies. However, that is not true that they that they are immune to the risk factors that can induce to a morbid states. (GUEDES, 1999) So,the main purpose of the present job to show the level of physical activity in the teenagers in the secondary school and to check their physical practices in the free times. They were asked over about 260 scholars in the period 53,!% female and 46,9% males. We concluded that 52,7% of them had kind of activity and 47,3% made them selves sedentary. Those who had an inactive life, 66,6% were woman. Those who had a good level of physical activity, or games frequently three times a week and 31,4% two time a week. As conclusion about the reasons for being inactive, we find 41,46% do not have time, 21,95% laziness, 21,13% no money, 15,44% dislike being active. About other ways of entertainment, we find that: 42% like talking with friends, 32% watching TV, 16% playing in the streets, 10% playing computer games. As a final conclusion, we find that the routine of a teenager is not approved as the ideal way of living. Despite of the level of physical activity, it is necessaries to include more forms of exercises to increase and improve their quality of living.
Keywords: Teenagers; physical activity; school state.